Increased atmospheric carbon dioxide concentration: effects on eucalypt rust (Puccinia psidii), C:N ratio and essential oils in eucalypt clonal plantlets - Ghini, Raquel [UNESP]; Mac Leod, Rodrigo Estevam de Oliveira [UNESP]; Neto, A. Torre; Cardoso, D. C.; Bettiol, Wagner [UNESP]; Morais, L. A. S. de; Vique, B. (Wiley-Blackwell, 2014)
Evaluation of impacts of high CO2 atmospheric concentration is strategically important for the development of adaptation measures and sustainable crop management. The objective of this study was to evaluate the effects of increased atmospheric CO2 concentration on eucalypt rust (Puccinia psidii), C:N ratio, yield and chemical composition of essential oils and growth of eucalypt clonal plantlets. Two clones with different levels of rust resistance were studied: a Eucalyptus urophylla x E. camaldulensis hybrid (VM 01) and an E. urophylla (clone MN 463). The experiments were performed in open-top chambers (OTCs) with CO2 mean concentrations (mu mol mol(-1)) of 399 (unenclosed control), 412 (OTCs with ambient CO2 concentration) and 508 (OTCs with high CO2 concentration) and in closed chambers (CCs) with CO2 mean concentrations of 390, 405, 520 and 700. Increased atmospheric CO2 concentrations resulted in a decrease in rust pustules per leaf, uredinia per leaf area, spores per uredinia and area under the disease progress curve in VM 01 (hybrid) clonal plantlets. The disease did not occur in MN 463 clonal plantlets, which demonstrated that high CO2 concentrations did not change the level of rust resistance. Plant growth of the two clones was stimulated by up to 23% in height and 26% in stem diameter in OTCs and by 18% for both clones in CCs. An increased C:N ratio in leaves, stems and roots was observed only for the VM 01 clonal plantlets. Essential oils produced by VM 01 (2.8 g 100 g(-1)) and MN 463 (1.4 g 100 g(-1)), as well as the major essential oil compounds (80% 1.8-cineole for VM 01; 50% 1.8-cineole and 32% alpha-pinene for MN 463), were not altered. In this study, increased concentrations of atmospheric CO2 favourably impacted eucalypt growth and reduced rust severity, while not influencing the production of essential oils.